2005 Cotton Variety Trials in Florida: Early-Maturing Cultivars - David L. Wright; C. A. Smith; E. B. Baxley (EDIS)
This document is SS-AGR-33, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date April 2006.